(untitled) (Itinera, 2018)
The background thesis of the paper concerns the deep methodological continuity that binds Benjamin’s Project on the Parisian Passages to his book on the Trauerspiel. The starting point is offered then by the reprise of the connection between Benjamin’s micrology and the theological task of critically reconstituting the whole in its original sense. This connection is consequently developed in a consideration of the “passage” as a nominal substance. On this basis is focused the complementarity in Benjamin’s late philosophy between historical materialism and theological nominalism. From the intertwining between urban and linguistic spaces emerges the figure of modern city as a labyrinth. The last move consists in converting the labyrinth in a monad, that is in an intensive space of knowledge and experience of truth.